Kemampuan Berpikir Analitis Siswa dalam Menyelesaikan Soal Kontekstual Bilangan Berpangkat - Dahriyah Dahriyah; Annafi Awantagusnik (Mandalika Mathematics and Educations Journal, 2026)
This study aims to describe the analytical thinking ability of tenth-grade students in solving exponentiation problems. The research employed a qualitative descriptive approach involving 33 tenth-grade students of SMA Raudlatul Ulum Gondanglegi as the initial data source. Based on the test results, students were classified into three categories of analytical thinking ability, namely high, medium, and low. Furthermore, four students were purposively selected as research subjects for in-depth analysis. The research instruments consisted of one contextual problem and semi- structured interviews. Data were analyzed using the Miles and Huberman model. The findings indicate differences in the characteristics of students’ analytical thinking processes across ability categories, particularly at the stages of determining and testing problem-solving strategies.